2017
DOI: 10.1097/md.0000000000009034
|View full text |Cite
|
Sign up to set email alerts
|

Association between tea consumption and osteoporosis

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Finally, drinking green tea and exercising were factors associated with osteoporosis. A recent meta-analysis showed that consuming green tea can reduce the risk of osteoporosis and the risk of hip fracture [25], mainly through the action of polyphenols that mitigate BMD loss [26]. Exercising is well known to be inversely associated with osteoporosis and bone degenerative diseases in general [2729], supporting the validity of our results.…”
Section: Discussionsupporting
confidence: 83%
“…Finally, drinking green tea and exercising were factors associated with osteoporosis. A recent meta-analysis showed that consuming green tea can reduce the risk of osteoporosis and the risk of hip fracture [25], mainly through the action of polyphenols that mitigate BMD loss [26]. Exercising is well known to be inversely associated with osteoporosis and bone degenerative diseases in general [2729], supporting the validity of our results.…”
Section: Discussionsupporting
confidence: 83%
“…Studies about polyphenols and their role in reducing the risk of osteoporosis were reported. A meta-analysis based on 17 journal articles using the keywords “tea and osteoporosis” was reported [ 59 ], concluding that consuming tea that contains polyphenols could reduce the risk of osteoporosis in all examined subgroups. Dietary intake of polyphenols in red wine extract resulted in a remarkable effect on bone strength improvement and prevention of osteopenia in estrogen-deficient ovariectomized rats [ 60 ].…”
Section: Bone and Osteoporosismentioning
confidence: 99%
“…Additionally, supplementation did not alter the serum calcium level and calcium excretion [ 69 ]. In fact, a meta-analysis showed that tea consumption decreased the risk of osteoporosis [ 70 ]. According to Zhang et al, subjects drinking tea presented a higher BMD of the hip and femoral neck than non-drinkers.…”
Section: Teamentioning
confidence: 99%